ANALISIS KANDUNGAN FENOLIK EKSTRAK DAUN JATI (Tectona grandis L.) DENGAN WAKTU DEKOMPOSISI YANG BERBEDA - Astiti, Ni Putu Adriani (Metamorfosa: Journal of Biological Sciences, 2017)
Teak ( Tectona grandis L.) is a plant with strong wood and is resistant to pests and diseases. In addition, its leaf extract is widely used by public as an additive in foods both as a preservative and as an alternative food coloring. The objective of this research was to determine phenolic compounds of teak leaves extracted with three different decomposition times (one, two and three weeks of decomposition). Extraction was conducted by using maceration method in which water was used as solvent. Identification of Phenolics was done by using Gas Chromatography. The results showed that the compounds of vanilic acid, salicylic acid, ferulic acid, cumaric acid, gallic acid, benzoic acid and cafeic acid were identified in the analysis. The concentration and composition of phenolic compounds in the extract was determined by decomposition.
Keywords: Teak (Tectona grandis L.), leaf extract, decomposition, phenolics